SUPPLY CHAIN INTEGRATION IN FASHION INDUSTRY, BANDUNG CITY - Hakim, Marsha Aulia (Advances in Social Sciences Research Journal, 2020)
The Fashion Industry in Indonesia is one of the industries with the most businesses. This makes this industry have a high level of competition. The higher level of competition will require a good flow of information in each supply chain. Each stage in the supply chain is an important aspect, especially in terms of distribution of both goods and information. The implementation of supply chain integration will help businesses to collaborate throughout the supply chain. The greater number of distribution channels both in downstream and upstream each business will need supply chain integration. This research will be conducted with descriptive analysis and qualitative methods. Researchers will conduct interviews directly to businesses in the fashion industry, especially who made their own products. The results of this research is the supply chain integration carried out at the upstream part of the supply chain, the business actors are still very competitive with other business actors because the raw material taken is not much so they are not immediately given a specialization by the supplier. Whereas in the downstream part of the supply chain, businesses have various promotions carried out new customers.